Ketidakbakuan Struktur Kalimat Bahasa Indonesia Pada Pemelajar BIPA Tingkat A2 Universitas Muhammadiyah Malang - Nur Hidayah Alifiani; Fauzan; Gigit Mujianto; Faizin (Universitas Muhammadiyah Jember, 2023)
BIPA (Bahasa Indonesia for Foreign Speaker) is a Bahasa Indonesia teaching program for foreign speaker. In this program, foreign speakers or students are grouped into three levels, beginner (A), intermediate (B), and advanced (C) levels. Aspects of language skills in BIPA learning are reading, listening, speaking, and writing. This article aims to find out the irregularity of Bahasa Indonesia sentence structure and the irregularity of writing sentence structure in BIPA UMM students essays. This research was compiled using a qualitative method with a descriptive type. The source of the data in this study were sentences in BIPA UMM students essays in the A2 level writing skills class for the Mid Semester Examination. The result of data analysis from BIPA UMM student essays, found irregularity sentence structure and diction placement errors in student essays.